Oxygen-dependent catabolism of indole-3-acetic acid in Bradyrhizobium japonicum. - Egebo, L A (1991)
Some strains of Bradyrhizobium japonicum have the ability to catabolize indole-3-acetic acid (IAA). Examination of this catabolism in strain 110 by in vivo experiments has revealed an enzymatic activity catalyzing the degradation of IAA and 5-hydroxy-indole-3-acetic acid. The activity requires addition of the substrates for induction and is oxygen dependent. The highest activity is obtained when the concentration of inducer is 0.2 mM. Spectrophotometric data are consistent with the suggestion that the indole ring is broken during degradation of IAA. We hypothesize that the enzyme catalyzes an oxygen-consuming opening of the indole ring analogous to the one catalyzed by tryptophan 2,3-dioxygenase. The pattern of metabolite usage by known tryptophan-auxotrophic mutants and studies of metabolites by high-performance liquid chromatography indicate that anthranilic acid is a terminal degradation product in the proposed pathway.